Competência em informação e inclusão digital no Programa um computador por aluno - Santos, Raimundo Nonato Ribeiro dos (2014)
It presents the results of a research about the One Laptop Per Child Program at Ceará, in the perspective of Information Science and its studies on digital inclusion, information literacy, intellectual technologies, information policies and information system. The methodological approach proposed includes quantitative and qualitative research, desk research, participatory research and applied research. The results show that the information system of the One Laptop per Child Program (actors, devices, artifacts and information actions), analyzes the information literacy of the participants of the One Laptop Per Child Program at Ceará and ends with a proposal for Information Action (Workshop on Information Literacy)